Efek Kecemasan terhadap Peningkatan Tekanan Darah Penderita Pre OP ORIF - Moh Alimansur; Septinulalin Dwi Cahyaningrum (coba, 2015)
ORIF surgery is a difficult experience for nearly all patients because ORIF surgery can affect pain, the chances of disabled and dependent on others. Often the patient shows excessive attitude with anxiety they experienced related to all kinds of surgical procedures, excessive attitude of the patient in the form of anxiety is most likely to affect blood pressure. This research aims to know the relationship of the level of anxiety with increased blood pressure patients pre op ORIF. Methods the study was Correlation. As for the technique used is the purposive sampling with the sample as much as 6 respondents. Measuring instrument of data collection using a modification of the HARS questionnaire and tensimeter mercury. The research results obtained there is a relationship between anxiety level of blood pressure in patients with pre op ORIF. With evidence of the 6 respondents in the light level of anxiety (33.3%) have an average of 125 mmHg Sistole blood pressure and 85 mmHg Diastole, the anxiety of being (16.7%) had an average blood pressure of 140 mmHg Sistole Diastole and 90 mmHg and anxiety reaction flask 50.0%) weight (having blood pressure 160 mmHg Sistole Diastole and 93,3 mmHg.The conclusions of this research is that the level of anxiety affect blood pressure, the higher the score, the more anxiety increase Sistole Diastole and blood pressure. Therefore before operating actions done ORIF should give health workers counseling about surgical procedures to patients to reduce anxiety so it does not raise blood pressure. Key Words: Anxiety, Blood Pressure, Pre Op ORIF